2013
DOI: 10.1093/cid/cit391
|View full text |Cite
|
Sign up to set email alerts
|

Response to Rituximab-Based Therapy and Risk Factor Analysis in Epstein Barr Virus–Related Lymphoproliferative Disorder After Hematopoietic Stem Cell Transplant in Children and Adults: A Study From the Infectious Diseases Working Party of the European Group for Blood and Marrow Transplantation

Abstract: More than two-thirds of patients with EBV-related PTLD survived after rituximab-based treatment. Reduction of immunosuppression was associated with improved outcome, whereas older age, extranodal disease, and acute graft-vs-host disease predicted poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
185
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(244 citation statements)
references
References 30 publications
8
185
1
3
Order By: Relevance
“…4 The real incidence and prognosis of EBV disease are difficult to evaluate due to differences in the PCR methods used to test EBV DNA, the quantitative PCR thresholds for therapeutic intervention and the diversity of criteria for defining high-risk patients. 5 Efforts to improve immune responses by reducing immunosuppressive drugs remain as one of the cornerstones of management but are not applicable to patients with active GVHD; 6,7 thus, eliminating B lymphocytes with the anti-CD20 monoclonal ab Rituximab is the most feasible treatment. 7 In the current study we compare the incidence and prognosis of EBV-related complications between patients with baseline highrisk characteristics for PTLD and patients affected by refractory GVHD, prospectively monitored for EBV DNAemia with early institution of Rituximab as pre-emptive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4 The real incidence and prognosis of EBV disease are difficult to evaluate due to differences in the PCR methods used to test EBV DNA, the quantitative PCR thresholds for therapeutic intervention and the diversity of criteria for defining high-risk patients. 5 Efforts to improve immune responses by reducing immunosuppressive drugs remain as one of the cornerstones of management but are not applicable to patients with active GVHD; 6,7 thus, eliminating B lymphocytes with the anti-CD20 monoclonal ab Rituximab is the most feasible treatment. 7 In the current study we compare the incidence and prognosis of EBV-related complications between patients with baseline highrisk characteristics for PTLD and patients affected by refractory GVHD, prospectively monitored for EBV DNAemia with early institution of Rituximab as pre-emptive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of overall survival at 3 years was 47.3%. 94 Among patients with PTLD after SOT, a 3-year overall survival was 62% and the 3-year progression-free survival was 57%. 95 …”
Section: Management and Outcomementioning
confidence: 92%
“…In one large case analysis conducted by Styczynski et al, 94 patients with high-risk HSCT showed an overall mortality rate due to PTLD of 30%. The probability of overall survival at 3 years was 47.3%.…”
Section: Management and Outcomementioning
confidence: 99%
“…Analysis of the outcomes following different transplantations shows that after 1316 kidney transplantations, the incidence of PTLD was 1.9%, 9 after 834 liver transplantations, the incidence was 2.8%, 10 after heart transplantation, the incidence was 6.5%, and after heart and lung transplantation, the incidence was 5.2%. 11 The risk associated with allogeneic stem cell transplantation (ASCT) depends on the origin of the stem cells, ranging from 1.16% in the case of matched familial donors to 2.86% in the case of mismatched familial donors and 3.97% in the case of matched nonfamilial donors to 11.24% with mismatched nonfamilial donors, 12 and 2% after cord blood transplantation. 13 A four-item score to predict PTLD development after ASCT has been proposed ( Table 2) based on T-cell depletion, use of antithymocyte globulin, human leukocyte antigen (HLA) mismatch, and age.…”
mentioning
confidence: 99%